Human rights and the COVID-19 pandemic: a retrospective and prospective analysis. Issue 10371 (14th January 2023) - Gostin, Lawrence O; Friedman, Eric A; Hossain, Sara; Mukherjee, Joia; Zia-Zarifi, Saman; Clinton, Chelsea; Rugege, Umunyana; Buss, Paulo; Were, Miriam; Dhai, Ames
Summary: When the history of the COVID-19 pandemic is written, the failure of many states to live up to their human rights obligations should be a central narrative. The pandemic began with Wuhan officials in China suppressing information, silencing whistleblowers, and violating the freedom of expression and the right to health. Since then, COVID-19's effects have been profoundly unequal, both nationally and globally. These inequalities have emphatically highlighted how far countries are from meeting the supreme human rights command of non-discrimination, from achieving the highest attainable standard of health that is equally the right of all people everywhere, and from taking the human rights obligation of international assistance and cooperation seriously. We propose embedding human rights and equity within a transformed global health architecture as the necessary response to COVID-19's rights violations. This means vastly more funding from high-income countries to support low-income and middle-income countries in rights-based recoveries, plus implementing measures to ensure equitable distribution of COVID-19 medical technologies. We also emphasise structured approaches to funding and equitable distribution going forward, which includes embedding human rights into a new pandemic treaty. Above all, new legal instruments and mechanisms, from a right to health treaty to a fund for civil society right to health advocacy, are required so that the narratives of future health emergencies—and people's daily lives—are ones of equality and human rights.